HUBUNGAN DERAJAT ANEMIA DENGAN KEJADIAN PARTUS LAMA IBU BERSALIN DI PUSKESMAS BASSE SANGTEMPE KABUPATEN LUWU - Devi Syamsuddin, Sri (NHM PRESS, 2024)
Prolonged labor is a condition where labor has been going on for more than 18 hours before the baby is born (Sebghati & Chandraharan, 2017). Some mothers experience labor longer than other mothers. Some long labors occur due to the large size of the fetus and its abnormal position. (Lamen et al., 2019). Prolonged labor can cause fatigue in the uterus, where the uterine muscle tone cannot contract properly after delivery, so the risk of bleeding is higher (Salsabila, 2020). Crosssectional research design which aims to determine the relationship between anemia and prolonged labor. The type of data collected is secondary data. Sample of 39 mothers giving birth. Univariate and bivariate data analysis. Where to find out the influence between variables using the SPSS chi-square formula with a value of α<0.05. According to the results of the chi-square statistical test, a significant number or probability value (0.000) was obtained which was much lower than the standard significance of 0.05 or (p < α), so the Ho data was rejected and H1 was accepted, which means there is a relationship between the degree of anemia and the incidence of mother's long party. gave birth at the Basse Sangtempe Community Health Center, Luwu Regency.